Analysis Of MSME Interest Factors in Halal Certification in Madiun - Muhamad Riki; Tiara Widya Antikasari; Rasti Febrian Dwi Arinda (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: Halal certification is the process of obtaining a halal certificate through several stages to prove that the raw materials, production process and halal product assurance system of the company meet the established standards. Halal certification plays a role in realizing welfare, in accordance with Islamic teachings which require its followers to maintain the welfare of themselves and others. With halal certification, the guarantee of welfare for the community can be better maintained. The interest of Micro, Small and Medium Enterprises in participating in the halal certification program is an important factor in increasing competitiveness and consumer trust. This study aims to analyze the factors that influence the interest of Micro, Small and Medium Enterprises in Madiun City in managing halal certification. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with Micro, Small and Medium Enterprises and analysis of related documents. Based on data from the Madiun City Manpower, Cooperatives and Micro Small Enterprises Office, the number of MSME in Madiun City continues to increase every year. In 2020 there were 23,545 units, in 2021 there were 23,618 units, and in 2022 it had reached 23,672 units, and in 2023 it increased to 23,768 units. However, this is quite worrying, the number of MSME actors who are halal certified in June 2024 was only recorded at 6% or around 4,147 MSME actors from the total number of MSME in Madiun City that have been halal certified. The results of the study indicate that knowledge factors, certification costs, ease of process, and government support play a significant role in shaping the interest of business actors in participating in the halal certification program. In addition, awareness of the importance of halal certification for business sustainability is also a major driving factor. These findings are expected to be a reference for the government and stakeholders in designing policies that support the acceleration of halal certification for the interests of MSME.